Government Transparency and Public Communication: analysis of the "ghost employees" case in the Legislative Assembly of Maranhão, São Luís, Brazil (Comunicação & Inovação, 2017)
This article analyzes the role of public communication in supporting the right to information, through the use of digital tools on the Transparency Portal, addressing the damages that the absence of this right generates for society. The theoretical approach is based on, among other authors, Zémor, Matos, Bresser-Pereira. A qualitative methodology was used in the case study on the reaction of the Legislative Assembly of Maranhão (ALEMA) concerning the ghost employees" issue. The analysis found that the ALEMA transparency portal does not use public communication tools.
Keywords: Right to Information; Public Interest; Public Communication